Prospective Study of the Surgical Techniques Used in Primary Rhinoplasty on the Caucasian Nose and Comparison of the Preoperative and Postoperative Anthropometric Nose Measurements - Cezar Augusto Sarraf Berger; Renato da Silva Freitas; Osvaldo Malafaia; José Simão de Paula Pinto; Evaldo Dacheux Macedo Filho; Marcos Mocellin; Marina Serrato Coelho Fagundes (International Archives of Otorhinolaryngology, 2015)
Abstract